Biodegradable phase change materials with high latent heat: Preparation and application on Lentinus edodes storage. (1st December 2021) - Kong, Qi; Mu, Honglei; Han, Yanchao; Wu, Weijie; Tong, Chuan; Fang, Xiangjun; Liu, Ruiling; Chen, Hangjun; Gao, Haiyan
Highlights: Starch grafted acrylic acid were made into biodegradable PCMs. PCMs possessed significant water retention, cycle stability, thermal and biodegradability properties. Shelf life of Lentinus edodes delayed on treating with PCMs. Abstract: In order to develop biodegradable phase change materials (PCMs) with high latent heat for cold chain logistics, superabsorbent resin (SAR) was prepared based on starch graft copolymerization. FTIR and DSC demonstrated that acrylic acid was successfully grafted onto starches and optimum latent heat of PCM was 330.4 J/g with 10% (w/w) starch. The water retention of PCM with 10% (w/w) starch was 0.49 after heating at 50 °C for 200 h, which was 4.9 folds higher than that of non-starch PCM. Biodegradation rate of PCM was 60.12% within 75-day burial, which was 6 folds higher than that of non-starch PCM. Moreover, significant reduction in browning index, odor, decay, relative conductivity and malondialdehyde (MDA) content was observed in Lentinus edodes treated by biodegradable PCM. These results indicated that the application of biodegradable PCM could extend the shelf life of fresh L. edodes stored at 25 °C.